Need analysis for developing an ethno-ESD science learning module based on Galendo local wisdom in elementary schools - Puti Hera Febiyan; Ghullam Hamdu (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2026)
Science learning in elementary schools remains predominantly textbook- oriented and insufficiently connected to students’ local cultural contexts, resulting in less meaningful learning experiences. Previous studies on ethnoscience and Education for Sustainable Development (ESD) have generally emphasized contextual learning; however, limited studies have explored the integration of ethnoscience and ESD in elementary science modules based on local food production practices. Therefore, this study aims to analyze the need for developing an Ethno-ESD-based science learning module grounded in galendo local wisdom in Tasikmalaya. This study employed a qualitative descriptive design involving nine elementary school teachers, six students, and three galendo entrepreneurs selected through purposive sampling. Data were collected through interviews, observations, document analysis, and content analysis, then analyzed using the Miles and Huberman interactive model. The findings indicate that existing instructional materials remain decontextualized and minimally integrate local culture, sustainability values, and inquiry-based activities. Students demonstrated higher engagement when science learning was connected to real-life experiences and local cultural practices. The galendoproduction process shows strong potential as an ethnoscience context because it reflects scientific concepts such as heat transfer, physical and chemical changes, and sustainability-oriented resource utilization practices. However, these aspects have not been systematically integrated into instructional modules currently used in schools. This study contributes by identifying the instructional needs and essential components required for developing an Ethno-ESD science module for elementary schools.